Technology and engineering strategies : step-by-step from theory into practice - Moar, P. J. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This pioneering book is the first-ever practical guide to developing and communicating technology and engineering strategies. It presents a unique step-by-step method for creating robust, evidence-based strategy, known as the Five Dimensions Process (or 5DP). The book also introduces a host of original insights, including a new theory of technology, a novel approach to product innovation, and groundbreaking contributions to our understanding of technological risk. It describes many easy-to-use tools, both new and established, for supporting activities such as solution design, system monitoring, risk identification, project management, the development of personnel, and ethical decision making. The book brims with strategic and tactical advice on such topics as university collaboration, technical compatibility, data utilisation, product design, project cancellations, outsourcing, knowledge management, and risk mitigation. It is essential reading for technologists and engineers across all disciplines, technology and engineering leaders, and professional strategy consultants"--
The formalities. How organisations communicate strategies -- Key components. The parts that make the whole -- Scoping the subject. What should we expect from a strategy? -- The unexpected. In the realm where uncertainty is king -- A shadow of doubt. Why light rarely shines on the future -- The origins of uncertainty. 18 Sources of shock and surprise -- Strategy in mind. How our thoughts shape decisions -- A stake in the strategy. Understanding the parties that matter -- Do it right! Conflicting values in a complex world -- What's new? Succeed by innovating. Succeed by not innovating -- Navigating uncertainty. Getting to where we want to go -- A strategy blueprint. The five dimensions process -- Inputs and outputs. Lessons learned and how to apply them.
Keywords: Communication of technical information; Communication in organizations; Communication in engineering; Engineering -- Management; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Project Management